Targeting TOPK 1 sensitises tumour cells to radiation-induced damage by enhancing replication stress - Herbert, K; Puliyadi, R; Prevo, R; Rodriguez Berriguete, G; Ryan, A; Ramadan, K; Higgins, G (Springer Nature, 2020)
T-LAK-originated protein kinase (TOPK) overexpression is a feature of multiple cancers, yet is absent from most phenotypically normal tissues. As such, TOPK expression profiling and the development of TOPK-targeting pharmaceutical agents have raised hopes for its future potential in the development of targeted therapeutics. Results presented in this paper confirm the value of TOPK as a potential target for the treatment of solid tumours, and demonstrate the efficacy of a TOPK inhibitor (OTS964) when used in combination with radiation treatment. Using H460 and Calu-6 lung cancer xenograft models, we show that pharmaceutical inhibition of TOPK potentiates the efficacy of fractionated irradiation. Furthermore, we provide in vitro evidence that TOPK plays a hitherto unknown role during S phase, showing that TOPK depletion increases fork stalling and collapse under conditions of replication stress and exogenous DNA damage. Transient knockdown of TOPK was shown to impair recovery from fork stalling and to increase the formation of replication-associated single-stranded DNA foci in H460 lung cancer cells. We also show that TOPK interacts directly with CHK1 and Cdc25c, two key players in the checkpoint signalling pathway activated after replication fork collapse. This study thus provides novel insights into the mechanism by which TOPK activity supports the survival of cancer cells, facilitating checkpoint signalling in response to replication stress and DNA damage.